Managing virtual teams - Ivanaj, Silvester; Bozon, Claire (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar Publishing, 2016)
'Managing Virtual Teams' explores the critical elements that must be considered in managing virtual teams in organizations from structural, managerial, and process points-of-view. Based in solid research, the book provides a deep look at the nature of virtual teams and the factors that enable their success. Using a text-analysis method, it consolidates results from both academic and practitioners' sources about virtual team inputs, processes, and outcomes. It lays out in clear detail the key characteristics of virtual teams and traces their emergence within organizations and research literature.
PART IV: OUTPUTS: VIRTUAL TEAMS A SOURCE OF PERFORMANCE9 Teamwork performance in virtual teams; 10 Affective performance in virtual teams; 11 Final conclusions; PART V: CASE STUDIES; 12 Case studies; References; Index
Includes bibliographical references (pages 257-293) and index.
Keywords: Virtual work teams -- Management